Resistance or change in Vietnamese Accounting? - Nguyen, L; Hooper, K; Sinclair, R (Virtus Interpress, 2013)
Research objective To explore the probability of substantive change in the Vietnamese accounting field, given that as approached from Bourdieu’s perspective of the “habitus”, most participants are likely, but not necessarily, to react conservatively to change. Research outcome From the viewpoint of the silent, dominated majority of bookkeepers in Vietnam, changes to the structure of the accounting field and to practice methods are not welcomed. However, the findings indicate that although they view real change as unlikely most of the 2,000 professional accountants are more positive. Research Questions: Do the 2 million practitioners in the Vietnamese accounting field look forward to changes that may be brought about by Anglo Saxon institutions such as, the large accounting firms, the international standards and the foreign accounting professions? Research Methods: Semi structured interviews were conducted to draw from respondents their feelings and thoughts on the possibility of change. Some 44 interviews of mostly bookkeepers, including some accountants, academics and other informed observers were conducted. Findings Of the 44 interviewees the bookkeepers were generally negative with regard to change. They preferred a compliance mode of accounting, which relied on government instructions as to suitable accounting treatments and served also the needs of tax accounting. By contrast, those representative of other groups such as professional accountants, managers and academics were more open to change and saw merit following accounting principles rather than government rules. Originality/value: The literature refers to “a paucity of studies on developing countries” with respect to the effects of exogenous changes to local accounting fields. The paper explores the Vietnamese accounting field to assess the extent and effects of such exogenous induced changes among the practitioners in the field.
Keywords: Vietnam; Bourdieu; Field